Acceptance of 2009 H1N1 Influenza Vaccine among Pregnant Women in Delaware - Drees, Marci; Johnson, Oluwakemi; Wong, Esther; Stewart, Ashley; Ferisin, Stephanie; Silverman, Paul R.; Ehrenthal, Deborah B. (American Journal of Perinatology, 2012)
Due to disproportionately high mortality from 2009 H1N1 influenza, pregnant women were given highest priority for H1N1 vaccination. We surveyed postpartum women to determine vaccine uptake and reasons for lack of vaccination. We performed a cross-sectional survey of postpartum women delivering at our institution from February 1 to April 15, 2010. The 12-question survey ascertained maternal characteristics and vaccination concerns. Among 307 postpartum women, 191 (62%) had received H1N1 vaccination and 98 (32%) had declined. Factors associated with H1N1 vaccination included older age (relative risk [RR] 1.3, 95% confidence interval [CI] 1.1 to 1.5 for age ≥35 years compared with 20 to 34 years), at least college education (RR 1.5, 95% CI 1.3 to 1.8), prior influenza vaccination (RR 1.6, 95% CI 1.3 to 2.0), provider recommendation (RR 3.9, 95% CI 2.1 to 7.4), vaccination of family members (RR 1.6, 95% CI 1.3 to 1.9), and receipt of seasonal influenza vaccination (RR 2.2, 95% CI 1.7 to 2.9). Non-Hispanic black women were less likely to have been vaccinated (RR 0.6, 95% CI 0.5 to 0.8) than non-Hispanic white women. Safety concerns were cited by the majority (66%) of nonvaccinated women. H1N1 vaccine uptake among pregnant women was substantially higher than reported influenza vaccination rates during previous seasons. Safety concerns were the major barrier to vaccination.
Keywords: H1N1 influenza; vaccination; pregnancy